2000
DOI: 10.2190/87h6-ra7j-v9k9-0u21
|View full text |Cite
|
Sign up to set email alerts
|

Computer and Internet Usage in Education: Theories, Practices, and Research Basics

Abstract: This article covered the theories, practices, and the research basics of the computer and Internet usage in education. The article reviewed the studies of computer and Internet usage in education and the practices of computer and Internet in open and distance learning, then discussed the two participants in effective online education, ended with reviewing on the researches about the demographic and socioeconomic characteristics of the users. The implication of this research is that computer and Internet usage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is somewhat heartening to know that "interpersonal" interactions with students was not a major concern to faculty. This finding bodes well for inevitable growth of online teaching in the future since it has always been considered a perennial "problem" area and one of the essential elements to constructive faculty-student interaction [34,38]. Such faculty views on the benefits of Internet use in teaching echoes a positive note for the future of computer-based instruction.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…It is somewhat heartening to know that "interpersonal" interactions with students was not a major concern to faculty. This finding bodes well for inevitable growth of online teaching in the future since it has always been considered a perennial "problem" area and one of the essential elements to constructive faculty-student interaction [34,38]. Such faculty views on the benefits of Internet use in teaching echoes a positive note for the future of computer-based instruction.…”
Section: Resultsmentioning
confidence: 72%
“…Future studies should shed some light on whether the passage of time will eventually bring attitudes toward instructional use of online approaches more in line with the actual use of computer-based didactic tools. Only then will instructors be truly "empowered" in the age of the Internet, as noted by Gray and Cao [34].…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with studies that found that students learn better in groups than individuals (Brown & Adler, 2008) and in line with Boss and Krauss's (2007) study that used similar methods to build knowledge through online learning experiences. Project-based learning enables students to engage in exploration, collaboration, free discussion, sharing ideas and exchanging information with each other (Gray & Xiaoli, 2001) to produce the final product for a given task. In using this project-based learning method, students acknowledge that discussions in the group make learning fun, reduce boredom, enhance ideas, and help students complete assigned tasks.…”
Section: Discussionmentioning
confidence: 99%